Parenting Program to Increase Awareness of Early Childhood Care - Daulay, Lily Sardiani; Sit, Masganti; Parapat, Ilham Karim; Elmi, Nur (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This research was conducted to determine the effectiveness of the parenting program "parent class" in increasing parents' awareness of early childhood care at Mutiara Zahra Kindergarten, Batang Kuis District, Deli Serdang Regency. This research is qualitative with a field study approach. The research was conducted at Mutiara Zahra Kindergarten, Batang Kuis District, Deli Serdang Regency. The research data is in the form of "parents class" activities given to parents at Mutiara Zahra Kindergarten. Data sources were obtained from the Principal and Parents. Data collection techniques are carried out by observation, seminars, interviews, and documentation. Data analysis is done by data reduction, data presentation, conclusion, and verification. The results of the study stated that the "parents class" activity conducted at Mutiara Zahra Kindergarten showed that the "parents class" activity was considered capable of increasing parents' awareness of Early Childhood Care.